Understanding Tax Amnesty and Tax Compliance in Indonesia: an Institutional Approach - Marko S Hermawan; Pamela Abigail; Yanthi Hutagaol Martowidodjo; Valentina Tohang (Universitas Hayam Wuruk Perbanas, 2019)
This study was motivated by one of President Joko Widodo’s projects, which is to build better infrastructure in Indonesia. Tax amnesty is used as a way of receiving undeclared assets expecting that Indonesia revenues will increase. This study focuses on the perception of both tax consultants and taxpayers. The interview was conducted to explore the points of interest as it was being developed. The analysis was done using institutional theory, analysis and discussion on their behavior towards tax amnesty are given based on the result of the research. This research uses interpretivism perspective to examine the meaning created by a human that differentiate human from physical phenomena. The data were collected from secondary data, archival data and complemented with semi-structured interviews. The finding suggests three themes associated with institutionalization of taxpayer compliance, namely rules and regulation, political economy, and social powers. These themes generate pressures on coercive isomorphism, as well as normative isomorphism. The result suggests establishing synergy and a dialectical process between the tax authorities and the taxpayer in conducting coaching, monitoring and fair enforcing of law to support taxpayer compliance.